1989
DOI: 10.1002/j.1537-2197.1989.tb11290.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Predatory and Fungivorous Mites in Leaf Domatia

Abstract: Domatia are small invaginations and hair tufts usually found at vein junctions on the undersides of leaves in many woody dicots. Domatia of 32 plant species (of worldwide origin from 18 families) growing in California, Hawaii, and Costa Rica were examined for mites. Domatia of 31 of 32 (97%) of these plants contained mites, and 24 of 32 (75%) contained mite eggs. Mites were found within the domatia of 48% of the sampled leaves. The domatia of 26 of 31 (84%) plants had mite species considered beneficial (primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1
17

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 9 publications
4
91
1
17
Order By: Relevance
“…Despite this, several mite species have been found in association with leaf domatia of C. arabica plants in Australia (O'Dowd 1994), Brazil (Matos et al 2006, Mineiro et al 2008, Costa Rica (Vega et al 2007), and Hawaii, USA (Pemberton & Turner 1989). In addition, recent studies have showed that coffee domatia improve survival and reproduction of the predatory mite Iphiseiodes zuluagai Denmark & Muma in southeastern Brazil (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, several mite species have been found in association with leaf domatia of C. arabica plants in Australia (O'Dowd 1994), Brazil (Matos et al 2006, Mineiro et al 2008, Costa Rica (Vega et al 2007), and Hawaii, USA (Pemberton & Turner 1989). In addition, recent studies have showed that coffee domatia improve survival and reproduction of the predatory mite Iphiseiodes zuluagai Denmark & Muma in southeastern Brazil (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf domatia are examples of such structures. They are small pockets, cavities, pits, and/or tufts of trichomes located at the junction of primary and secondary veins on the leaf undersurface (Metcalfe and Chalk, 1979;Pemberton and Turner, 1989;Turner and Pemberton, 1989;Walter and O'Dowd, 1992;Whitman, 1994). Studies in which domatia were sampled for their occupants showed that many contained mites, predominantly predatory or fungivorous species Karban, 1997; O'Dowd and Pemberton, 1998).…”
Section: Plants Provide Sheltermentioning
confidence: 99%
“…It has been hypothesised that leaf domatia mediate mutualistic interactions between plants and predatory and fungivorous mites because they protect the mites against adverse conditions ( Pemberton & Turner, 1989;O'Dowd & Willson, 1991;Grostal & O'Dowd, 1994 ;Walter, 1996 ) and against other predators or omnivores ( Norton et al , 2001;Faraji et al , 2002a , b). Owing to this protection, the survival of predators on plants with domatia would be higher than on plants without domatia ( Agrawal & Karban, 1997;Agrawal et al , 2000;English-Loeb et al , 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this indirect defence, plants produce herbivore-induced volatiles to attract predators and parasitoids ( Dicke, 1999;Janssen et al , 2002;Kessler & Baldwin, 2002 ), offer pollen and nectar as alternative food to the enemies ( Beattie, 1985;Pemberton & Lee, 1996;Sabelis & van Rijn, 1997 ), or provide shelter to natural enemies ( Beattie, 1985;O'Dowd & Willson, 1989;Pemberton & Turner, 1989;O'Dowd & Willson, 1991;Walter, 1996 ). Examples of shelter provided by plants are leaf domatia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation